2023
DOI: 10.1002/jsfa.12393
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of deoxynivalenol in wheat by double dielectric barrier discharge cold plasma: identification and pathway of degradation products

Abstract: Background: Deoxynivalenol (DON) produced during the onset of fusarium head blight not only affects the quality and safety of wheat but also causes serious harm to human and livestock health. However, due to the high stability of DON, it is difficult to eliminate it or reduce it naturally after it has been produced. Cold plasma technology is a non-thermophysical processing technology that has been widely used for microbial inactivation and mycotoxin degradation. In this study, the degradation efficiency of dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…From the results interpreted, NTP is found to successfully degrade mycotoxins, especially DON produced by Fusarium spp., and mycotoxins from other phytopathogens from different studies. Zhang et al [ 63 ] subjected DON mycotoxin solution to optimized conditions of double dielectric barrier discharge, only to find degradation of 98.94% within 25 min of plasma treatment. Ott et al [ 64 ] also confirmed the degradation of more than 99% of 100 μg DON mycotoxin in aqueous suspensions after 21 min of direct high voltage atmospheric cold plasma treatment, using air to generate reactive oxygen and reactive nitrogen species.…”
Section: Discussionmentioning
confidence: 99%
“…From the results interpreted, NTP is found to successfully degrade mycotoxins, especially DON produced by Fusarium spp., and mycotoxins from other phytopathogens from different studies. Zhang et al [ 63 ] subjected DON mycotoxin solution to optimized conditions of double dielectric barrier discharge, only to find degradation of 98.94% within 25 min of plasma treatment. Ott et al [ 64 ] also confirmed the degradation of more than 99% of 100 μg DON mycotoxin in aqueous suspensions after 21 min of direct high voltage atmospheric cold plasma treatment, using air to generate reactive oxygen and reactive nitrogen species.…”
Section: Discussionmentioning
confidence: 99%